Biochemical and Histological Biomarkers in Crassostrea sp. (Bivalvia, Ostreidae) for Environmental Monitoring of a Neotropical Estuarine Area (São José Bay, Northeastern Brazil) - Noleto, Katherine Saldanha (2021)
This study aimed to compare biochemical and histological biomarkers in oysters to identify impacted areas in a Brazilian port region. Oysters belonging to the Crassostrea genus were collected in two points in São José Bay (Brazil): (A1) Curupu Island (control area) and (A2) Braga Port (impacted area). Digestive glands from oysters were used to analyze the enzymatic activity of glutathione S-transferase and Catalase. The gills were used for standard histology analyses. Water samples were collected for metal analyses. Our results indicated that there was a change in the activity of oyster GST and CAT enzymes, especially in A2. Histological gill analysis indicated more frequent changes in A2. The analyzed metals presented higher values in A2. The results of this study suggest that enzymatic alterations, histological changes and higher metal values are indicative of initial stress caused by contaminants in São José Bay, especially in the port region.